(untitled) (International journal of artificial intelligence, 2026)
Hopper dosers represent a critical class of bulk material handling equipment widely employed across pharmaceutical, food processing, chemical, and construction industries. Despite their industrial prevalence, a consolidated technical review encompassing their structural design, operational principles, control technologies, and comparative performance has not been published in recent literature.